Reflections of students on their community drugstore and hospital pharmacy internship program - Nacabu-an, Shiela May Jayme
Pharmacy internship program in community and hospital are good venues for students to learn the competencies required of a pharmacists in a patient-centered practice, apply what they learned in school, and appreciate their roles in the future. However, there were limited studies on the effects of hospital and community drugstore internship to pharmacy students in the country. The study determined the effects of community drugstore and hospital pharmacy internship programs on the development of competencies among UP pharmacy students based on the students' reflections of their experiences. The students' reflections of their learning based on their activities were described in the study and the competencies learned before and after the internship programs were determined. This study employed a descriptive quantitative, cross-sectional study design using survey, records review, focus group discussions (FGDs), and interviews. The study included 36 3rd year community drugstore interns and 33 4th year hospital pharmacy interns from BS Pharmacy and BS Industrial Pharmacy programs for 2011. Pre-test and post-test questionnaires were distributed to assess the competencies of students. The records reviewed included students' notes, exit examinations scores, FGDs, and interviews and were used to describe their experiences and reflective learning if they perceived that they learned the required competencies during their internship. Results showed that the interns developed all the competencies to practice pharmacy in the country despite the differences in the actual practice and the FIP/WHO standard of pharmacy practice. The community pharmacy interns showed lack of interest to pursue their field for major internship unlike the hospital interns. This is significant as the pharmacy profession aims to provide a patient-centered pharmaceutical care in hospital and community drugstores and the recent implementation of Return Service Agreement of UP Manila as an answer to the decrease in professionals practicing in the country.